The influence of different proportions of rumen degradable protein and non-fiber carbohydrate consisted in feed ration on in vitro rumen fermentation, digestibility, gas production kinetics and enteric methane emission - Tanuwiria, Ujang Hidayat; Zain, Mardiati; Syamsu, Jasmal Ahmari; Yunilas, Yunilas; Mushawwir, Andi; Yanza, Yulianri Rizki (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The present study aimed to determine the influence of different rumen degradable protein (RDP)/non-fibrous carbohydrate (NFC) proportions on ruminal fermentation characteristics, gas production kinetics, and microbial populations. Materials and Methods: An in vitro batch culture trial was conducted using different combinations of RDP/NFC proportions categorized into six dietary treatments (n = 5 per treatment, three replicative runs). Combinations of balanced RDP/NFC proportions were 60% RDP: 35% NFC (P1, 1:3.65), 60% RDP: 40% NFC (P2, 1:4.17), 65% RDP: 35% NFC (P3, 1:3.37), 65% RDP: 40% NFC (P4, 1:3.85), 55% RDP: 39% NFC (P5, 1:5.06), and 55% RDP: 41% NFC (P6, 1:5.32). Results: The present study observed that the combination of a high proportion of RDP and NFC influenced in vitro rumen fermentation, such as volatile fatty acid and NH₃ concentrations, and in vitro organic matter digestibility. However, a high RDP (65%) with a low NFC (35%) positively influenced total gas production, gas kinetics, enteric methane production, and microbial population in the rumen. Conclusion: In this study, we revealed that the ratios of RDP and NFC in animal feed have a considerable impact on rumen fermentation, microbial population, and digestibility. J. Adv. Vet. Anim. Res., 12(3): 784–794, September 2025 http://doi.org/10.5455/javar.2025.l941